Antipsychotic-associated psoriatic rash – a case report - Camelia-Eugenia Bujor; Torkel Vang; Jimmi Nielsen; Ole Schjerning (BMC Psychiatry, 2017)
Abstract Background Antipsychotics are a heterogeneous group of drugs. Although, antipsychotics have been used for years, unexpected side effects may still occur. With this case report we focus on a possible association between psoriasis and antipsychotics. Data on the patient’s course of psychiatric disease, onset of psoriasis and its evolution were extracted from the patient’s medical files. Case presentation We present a case of a 21-year-old female diagnosed with schizophrenia. She was initially treated with quetiapine, and later switched to aripiprazole due to weight gain. After initiation of antipsychotic treatment, the patient suffered from severe psoriasis lesions. Conclusions Antipsychotics may possess immunological properties that may be involved in immune-mediated conditions, such as psoriatic rash. Further studies are warranted to determine causality and mechanism.